PENGARUH METODE PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KEMAHIRAN GRAMMAR SUBJECT-VERB AGREEMENT - Gufron (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The purpose of this study was to find out the impact of the flipped classroom method on students' subject-verb agreement grammar skills. This research was conducted in an English for Specific Purposes (ESP) class of intermediate level where students from the pharmacy major at a private university in Jakarta. The research design was quasi-experimental by dividing the respondents into two groups, namely the control and experimental groups. The experimental group participated in 15 weeks of learning grammar of subject verb agreement using the flipped classroom method, while the control group used the traditional method. The results of the data analysis show that the use of the flipped classroom method can improve students' subject-verb agreement skills. The flip method also increases student motivation because students master the material taught in class by studying it before class begins through an online Learning Management System.